Mitomycin immunoblot colony assay for detection of Shiga-like toxin-producing Escherichia coli in fecal samples: comparison with DNA probes. - Hull, A E (1993)
We developed a direct screening immunoblot assay for the detection of Shiga-like toxin (SLT)-producing organisms in stool samples. The assay takes advantage of the phage-mediated nature of SLT production in Escherichia coli and the phage-inducing effects of mitomycin. The addition of mitomycin significantly enhanced the amount of toxin available for immunologic detection. By using the mitomycin-enhanced immunoblot assay, SLT-producing E. coli could be distinguished from non-toxin-producing E. coli and normal stool flora in ratios of 1:1,000 to 1:5,000. The immunoblot assay was examined in a field setting and compared with direct DNA probing for SLT-I and SLT-II. The assay was able to detect SLT-producing E. coli with a high level of sensitivity and specificity. Specificity was markedly improved by using a monoclonal antibody which cross-reacts with both SLT-I and SLT-II B subunits in place of the polyclonal antitoxin sera. We conclude that the mitomycin-enhanced immunoblot colony assay is a rapid and reliable alternative to DNA probing for the detection of phage-mediated SLT-producing organisms in stool samples, especially when the production and use of nucleic acid probes are not feasible. In addition, it permits isolation of positive colonies for further study and confirmation.